2017
DOI: 10.1016/j.compstruct.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Large-deflection and post-buckling analyses of laminated composite beams by Carrera Unified Formulation

Abstract: The Carrera Unified Formulation (CUF) was recently extended to deal with the geometric nonlinear analysis of solid cross-section and thin-walled metallic beams [1]. The promising results provided enough confidence for exploring the capabilities of that methodology when dealing with large displacements and post-buckling response of composite laminated beams, which is the subject of the present work. Accordingly, by employing CUF, governing nonlinear equations of low-to higher-order beam theories for laminated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…In the field of buckling and post-buckling analyses, many researchers have extensively investigated these behaviors for composite beams and plates without considering the damage effects. Turvey and Marshall (1995) and Argyris and Tenek (1997) published excellent reviews on past studies of buckling and post-buckling of structures using different methods and recently, Pagani and Carrera (2017) have analyzed the large deflection and post-buckling behaviors of laminated beams by Carrera unified formulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of buckling and post-buckling analyses, many researchers have extensively investigated these behaviors for composite beams and plates without considering the damage effects. Turvey and Marshall (1995) and Argyris and Tenek (1997) published excellent reviews on past studies of buckling and post-buckling of structures using different methods and recently, Pagani and Carrera (2017) have analyzed the large deflection and post-buckling behaviors of laminated beams by Carrera unified formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to this approach, the derivation of a family of higher-order beam theories is made formally general regardless of the through-the-thickness approximating functions and the approximation order. UF has been extended to large deflections and postbuckling analysis of beam structures in recent works by Pagani and Carrera [20,21], where the capability of such approach to investigate global and local deformations in solid and thin-walled beam structures was demonstrated by using Lagrange polynomials as approximating functions for the cross-section kinematics within a layer-wise approach. An elastoplastic analysis via UF-based one-dimensional finite elements has been carried out by Carrera et al [22], showing that such formulation can lead to a 3D-like accuracy in terms of displacements and stresses for compact and thin-walled structures subjected to localized loadings.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the stress prediction is concerned, once the second Piola-Kirchoff stresses have been obtained by the TL formulation, they are transformed into the true Cauchy stresses to have a direct comparison with results coming from updated Lagrangian formulations implemented in the commercial software ANSYS. As opposed to the Lagrange layer-wise approximation [20,21], in both linear and nonlinear analyses, the use of Taylor polynomials allows an enrichment of the cross-sectional kinematics by simply increasing the order N and with no need for additional crosssectional nodes. This feature makes Taylor-based refined models particularly suitable for the analysis of multilayered structures in the framework of an equivalent single-layer approach that will be presented in a future work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of the framework is derived from the ability of CUF models to provide accurate 3D displacement and stress fields at a reduced computational cost (approximately one order of magnitude of degrees of freedom less as compared to standard 3D brick elements) [24,25,27]. Over the last couple of decades, CUF models have been extensively used for wide range of structural simulations such as static analysis of laminated beams [28], dynamic response for aerospace structures [29], vibration characteristics of rotating structures [30], evaluation of failure indices in composite structures [26], buckling and post-buckling analysis of compact and composite structures [31,32]. Carrera et al reported an extended review of recent developments in refined theories for beam based on CUF with particular focus on diverse applications [33].…”
mentioning
confidence: 99%